6 - Book Reviews: Gendering African History - Zeleza, Paul Tiyambe (Africa Development, 1993)
A Review of Jane L. Parpart and Kathleen A. Staudt, eds. Women and the State in Africa. Boulder and London: Lynne Rienner, 1989, 229 pp.; Sharon Stichter and Jane L. Parpart, eds. Women , Employment and the Family in the International Division of Labour. Philadelphia: Temple University Press, 1990. 253pp.; Luise White. The Comforts of the Home: Pļostitution in Colonial Nairobi . Chicago and London: University of Chicago Press, 1990. 285 pp.; and Family , State , and Economy in Africa , Special Issue, Signs: Journal of Women in Culture and Society 16, No.4 (Summer, 1991).